Agricultural Applications of Antarctic Bacteria and Fungi - da Silva, Averlane Vieira; da Silva, Mayanne Karla; de Souza Silva, Adriely Vital; da Silva Costa, Rafaela Ferreira; de Oliveira, Adeildo Júnior; da Silva, Maria Nicolle Pereira; de Queiroz, Aline Cavalcanti; Moreira, Magna Suzana Alexandre; da Silva, Andressa Letícia Lopes; Ottoni, Júlia Ronzella; Passarini, Michel Rodrigo Zambrano; Sette, Lara Durães [UNESP]; et al. (Springer Nature, 2025)
Antarctica is a natural laboratory, an environment with limiting characteristics for developing all life forms. Microorganisms are the life forms most adapted to the different Antarctic ecological niches and directly influence the development of mosses and the two angiosperms that occur at the South Pole. The aim of this review is to present the main biotechnological applications for use in the agricultural sector that fungi and bacteria isolated from Antarctica have been prospected in recent literature. In this sense, bacteria and fungi isolated from Antarctica have been reported to have biological activities of agricultural interest, including the production of metabolites related to phosphate solubilization, nitrogen fixation, phytohormones such as indole-3-acetic acid (IAA), substances with herbicidal and phytopathogen-inhibiting activities. Furthermore, as they are adapted to the different adverse conditions of Antarctica, understanding the possible applications of Antarctic fungi and bacteria could help in the near future to boost the intensification of agriculture sustainably, with the production of bioinoculants, for example, especially in a scenario of global climate change.